Singlet oxygen scavenging activity of plastoquinol in photosystem II of higher plants: electron paramagnetic resonance spin-trapping study - Yadav, Deepak Kumar; Kruk, Jerzy; Sinha, Rakesh Kumar; Pospíšil, Pavel (Biochimica et biophysica acta, 2010)
Singlet oxygen (¹O₂) scavenging activity of plastoquinol in photosystem II (PSII) of higher plants was studied by electron paramagnetic resonance (EPR) spin-trapping technique. It is demonstrated here that illumination of spinach PSII membranes deprived of intrinsic plastoquinone results in ¹O₂ formation, as monitored by TEMPONE EPR signal. Interestingly, the addition of exogenous plastoquinol (PQH₂-1) to PQ-depleted PSII membranes significantly suppressed TEMPONE EPR signal. The presence of exogenous plastoquinols with a different side-chain length (PQH₂-n, n isoprenoid units in the side chain) caused a similar extent of ¹O₂ scavenging activity. These observations reveal that plastoquinol exogenously added to PQ-depleted PSII membranes serves as efficient scavenger of ¹O₂.
Keywords: Spin Trapping; buněčná membrána; Plastoquinone; Free Radical Scavengers; Photosystem II Protein Complex; fotosystém II (proteinový komplex); Electron Spin Resonance Spectroscopy; singletový kyslík; Spinacia oleracea; Cell Membrane; Singlet Oxygen; spin trapping; plastochinon; elektronová paramagnetická rezonance; scavengery volných radikálů